Relationship between fear of failure, creative process engagement and self-related creativity among Malaysian undergraduates - Lim, Jason Tau Yi; Tan, Wei Sen; Tsai, Nicholas Chin Yao (2020)
This study was designed to study the relationship between fear of failure, creative process engagement, and self-rated creativity among Malaysian undergraduates. A quantitative cross-sectional correlational research design was employed. Participants were recruited using paper and pencil surveys through convenience sampling and snowball sampling. 414 Malaysian undergraduates within the age 18 to 29 were involved. The instruments Performance Failure Appraisal Inventory Short-Form (PFAI-SF), Creative Process Engagement Scale (CPES) and Self-rated Creativity Scale (SRCS) were used. Moreover, the Revised Cheek and Buss Shyness Scale (RCBS) and New General Self-Efficacy (NGSE) were also adopted for control variables of shyness and self-efficacy respectively in this study. Through correlational and mediational analysis, with shyness and self-efficacy being controlled, there was no significant relationship found between fear of failure and creative process engagement or self-rated creativity. Creative process engagement was also unable to mediate the relationship between fear of failure and self-rated creativity. However, creative process engagement was shown to be positively associated with self-rated creativity. Moreover, exploratory analysis was conducted and it was found that when fear of failure is being controlled, shyness is able to predict self-rated creativity but self-efficacy or creative process engagement also mediates the effect. Nonetheless, the present study has shed light for future studies as the exploratory analysis results have provided directions for future researchers to take into consideration.